2002
DOI: 10.1093/chromsci/40.9.477
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for Acetaldehyde Determination in Blood by High-Performance Liquid Chromatography and Solid-Phase Extraction

Abstract: This study reports on an improved method for acetaldehyde (ACH) determination in blood by high-performance liquid chromatography (HPLC). In the case of HPLC analysis, ACH is generally converted to derivatives for ultraviolet detection (for example 2,4-dinitrophenylhydrazine [DNPH] derivative). Nevertheless, elevation of the background during protein precipitation, hydrazone synthesis, or both frequently results in a serious loss of accuracy and precision of the analysis. The method in this study is developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…While most DNPH was removed from the cartridge with 1.5 ml of 70% methanol, AcH-DNP co-eluted in this washing step (data not shown),. This carryover effect resulted in either low efficiency of extraction or contamination with DNPH, as observed by other investigators (Kozutsumi et al, 2002; Ma and Klemm, 1997). Alternatively,, both AcH-DNP and DNPH were extracted by liquid-liquid extraction into an organic solvent (acetonitrile or isooctane) with negligible amounts remaining in the aqueous phase (data not shown).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…While most DNPH was removed from the cartridge with 1.5 ml of 70% methanol, AcH-DNP co-eluted in this washing step (data not shown),. This carryover effect resulted in either low efficiency of extraction or contamination with DNPH, as observed by other investigators (Kozutsumi et al, 2002; Ma and Klemm, 1997). Alternatively,, both AcH-DNP and DNPH were extracted by liquid-liquid extraction into an organic solvent (acetonitrile or isooctane) with negligible amounts remaining in the aqueous phase (data not shown).…”
Section: Resultsmentioning
confidence: 54%
“…The acid-catalyzed reaction had an optimum pH 4.0, since the rate-limiting step is the protonation of carbonyl oxygen, followed by the loss of water to form hydrazone. An optimum pH of 4.0 for the derivatization reaction was also found by Kozutsumi et al (2002), though stronger acidic conditions have been also reported (Bicking et al, 1988; Cotsaris and Nicholson, 1993). The reaction at the optimum pH was completed within 40 min at ambient temperature or with longer incubation at 4°C (see Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The most widely used derivatization agent is 2,4-dinitrophenylhydrazine (DNPH). In acidic media, DNPH reacted with carbonyl group of ACD to form Schiff base derivatization product DNPH-ACD [11,12] . The derivatization reaction leads to an orange colored mixture of DNPH-ACD as shown in fig.…”
mentioning
confidence: 99%
“…This is mainly due to the furtive nature of acetaldehyde, necessitating careful sample processing and detection methods such as spectrophotometry, nuclear magnetic resonance imaging (NMR), or gas chromatography mass-spectrometry (GC-MS), which typically result in processing and destruction of the sample. 14 The use of carbonyl-responsive fluorescent probes 1521 could potentially circumvent these problems by allowing for the real-time, unobtrusive visualization of acetaldehyde as it is produced in living cells.…”
mentioning
confidence: 99%